Trends in 3D bioprinting for esophageal tissue repair and reconstruction. (January 2021) - Farhat, Wissam; Chatelain, François; Marret, Auriane; Faivre, Lionel; Arakelian, Lousineh; Cattan, Pierre; Fuchs, Alexandra
Abstract: In esophageal pathologies, such as esophageal atresia, cancers, caustic burns, or post-operative stenosis, esophageal replacement is performed by using parts of the gastrointestinal tract to restore nutritional autonomy. However, this surgical procedure most often does not lead to complete functional recovery and is instead associated with many complications resulting in a decrease in the quality of life and survival rate. Esophageal tissue engineering (ETE) aims at repairing the defective esophagus and is considered as a promising therapeutic alternative. Noteworthy progress has recently been made in the ETE research area but strong challenges remain to replicate the structural and functional integrity of the esophagus with the approaches currently being developed. Within this context, 3D bioprinting is emerging as a new technology to facilitate the patterning of both cellular and acellular bioinks into well-organized 3D functional structures. Here, we present a comprehensive overview of the recent advances in tissue engineering for esophageal reconstruction with a specific focus on 3D bioprinting approaches in ETE. Current biofabrication techniques and bioink features are highlighted, and these are discussed in view of the complexity of the native esophagus that the designed substitute needs to replace. Finally, perspectives on recent strategies for fabricating other tubular organ substitutes via 3D bioprinting are discussed briefly for their potential in ETE applications.